TNFRp55 modulates IL-6 and nitric oxide responses following Yersinia lipopolysaccharide stimulation in peritoneal macrophages - Eliçabe, Ricardo Javier (2011)
While cytokines are major regulators of macrophage activation following host-pathogen interactions, they also act to limit inflammation to avoid tissue damage. In previous studies we reported the development of progressive Yersinia enterocolitica-induced reactive arthritis (ReA) in mice lacking the tumor necrosis factor receptor p55 (TNFRp55). In this work, we analyzed the response of TNFRp55⁻/⁻ macrophages to Y. enterocolitica antigens. We found higher concentration of nitric oxide (NO) in TNFRp55⁻/⁻ compared to wild-type macrophages in response to heat-killed Yersinia (HKY) and Yersinia outer membranes (OM). Moreover, Toll-like receptor (TLR)4 expression was increased in OM-stimulated TNFRp55⁻/⁻ versus wild-type (WT) macrophages. Accordingly, NO production was inhibited in TLR4-deficient macrophages following stimulation with OM, suggesting that LPS may function as a major OM component implicated in these responses. Thus, augmented NO production together with enhanced expression of inducible nitric oxide synthase (iNOS) and higher IL-6 production, may provide a pro-inflammatory setting in Yersinia LPS-stimulated TNFRp55⁻/⁻ macrophages. Augmented synthesis of NO and IL-6 was prevented by treatment with Polymyxin B, or by exposure to a specific NF-κB p65 oligonucleotide antisense, indicating the involvement of TLR4-mediated NF-κB activation in the unleashed pro-inflammatory response triggered by TNFRp55 deficiency. Thus, TNFRp55 modulates macrophage functions in response to Yersinia LPS stimulation through mechanisms involving NO, IL-6 and NF-κB pathways, suggesting an essential regulatory role of TNF via TNFRp55 signaling.